Hernández, Héctor H., Salvar vidas con el Derecho Penal. (Testimonio de un Defensor), Buenos Aires, Círculo Rojo, 2018, 165 pp. - Romero Berdullas, Carlos Manuel (2018)
Fil: Romero Berdullas, Carlos Manuel. Universidad del Salvador; Argentina